PENGELOLAAN KURIKULUM LEMBAGA KELOMPOK BERMAIN - Aisyah Nur'aini; Retno Wulandari (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2023)
This paper discusses Curriculum Management in Play Group Institutions. The data in this article were obtained from observing books, articles and the internet related to curriculum management for children, then this data was processed in their own language so as to obtain data that was in accordance with what was discussed. The results of this article show that there are several points related to curriculum management for children, namely the meaning, objectives, principles, components, and scope of curriculum management. It is hoped that this article can be used as study material for further discussions regarding curriculum management in children.